Optimal treatment of laryngopharyngeal reflux disease. (November 2013) - Martinucci, Irene; de Bortoli, Nicola; Savarino, Edoardo; Nacci, Andrea; Romeo, Salvatore Osvaldo; Bellini, Massimo; Savarino, Vincenzo; Fattori, Bruno; Marchi, Santino
Laryngopharyngeal reflux is defined as the reflux of gastric content into larynx and pharynx. A large number of data suggest the growing prevalence of laryngopharyngeal symptoms in patients with gastroesophageal reflux disease. However, laryngopharyngeal reflux is a multifactorial syndrome and gastroesophageal reflux disease is not the only cause involved in its pathogenesis. Current critical issues in diagnosing laryngopharyngeal reflux are many nonspecific laryngeal symptoms and signs, and poor sensitivity and specificity of all currently available diagnostic tests. Although it is a pragmatic clinical strategy to start with empiric trials of proton pump inhibitors, many patients with suspected laryngopharyngeal reflux have persistent symptoms despite maximal acid suppression therapy. Overall, there are scant conflicting results to assess the effect of reflux treatments (including dietary and lifestyle modification, medical treatment, antireflux surgery) on laryngopharyngeal reflux. The present review is aimed at critically discussing the current treatment options in patients with laryngopharyngeal reflux, and provides a perspective on the development of new therapies.